Nanoemulsões de óleos essenciais: mecanismos de estabilidade e interação com pectina em bionanocompósitos para aplicação em embalagens ativas - Lorevice, Marcos Vinicius (2019)
Microbial growth is among the challenges impairing food preservation and shelf-life. Essential oils (EO) featuring antimicrobial and antioxidant activities denote an alternative for lessening the contents of synthetic additives that may be harmful to human health. The limitations due the low EO solubility in water and their poor stability in aqueous media have been suppressed by the use of nanoemulsions (NE), which feature kinetic stability, intensify the antimicrobial effect of EO, and allow their dispersions in aqueous systems such as those involving polysaccharides for applications as packaging materials. The objective of this study were i) the production of NE having rosemary or clove EO as dispersed phase through high-energy (microfluidization - MF) or low-energy (catastrophic phase inversion - CPI) emulsification methods; ii) the evaluation of the NE stability with regard to the surfactant content in relation to the dispersed phase; and iii) the NE incorporation into pectin films to investigate the interaction among the components and the effect of the surfactant content on the physicochemical and active properties of the nanocomposites. The NE were characterized as to their average droplet sizes, zeta potentials, colloidal stability, and morphology. The films were evaluated as to their film-forming viscosity, morphology, wettability by water as well as mechanical, antimicrobial, and antioxidant properties. Regardless of the EO, the CPI-produced NE presented average droplet sizes and zeta potentials ranging from 100 to 500 nm and from -10 to -1 mV, respectively, being surfactant concentration and location the major factors affecting polydispersity. The MF was more efficient than CPI because the former led to average diameters ranging from 10 to 100 nm, and surfactant content was the dominant factor. The rosemary NE obtained through MF were more stable against creaming than clove NE against sedimentation. Cryo-TEM images indicate quasi-spherical particles with polydisperse diameters for CPI and homogeneous pattern for MF. Dynamic light scattering experiments did not evidence electrostatic interactions among pectin and surfactant, but the increased viscosity for surfactant contents between 10 and 20 wt.% suggested possible hydrophobic interactions, which led to films with increased hydrophobicity as well as sponge-like internal for both pectin/surfactant and pectin/NE films. The tensile strength and elastic modulus were decreased for surfactant contents higher than 20 wt.%. Rosemary EO exhibited antioxidant activity by capturing 85% of DPPH radicals and presenting an EC50% value of 50% of the initial EO concentration. The EC50% was decreased in the nanocomposites because of EO loss through evaporation upon drying, without any effect of the surfactant. On the other hand, antimicrobial activity was not detected because of the EO diffusion towards the culture medium, which was limited by the surfactant quantity and low oil-soluble in aqueous culture medium. This reported study is innovative because it relates the properties of pectin/rosemary NE nanocomposites with the content and characteristics of the surfactant, paving the route for a novel understanding on the role played by each component on the active and physicochemical properties.